PET and polyolefin plastics supply chains in Michigan: present and future systems analysis of environmental and socio-economic impacts - Chaudhari, Utkarsh S.; Sedaghatnia, Kamand; Reck, Barbara K.; Maguire, Kate; Johnson, Anne T.; Watkins, David W.; Handler, Robert M.; Hossain, Tasmin; Hartley, Damon S.; Thompson, Vicki S.; Peralta, Alejandra; Apriesnig, Jenny L.; et al. (Frontiers in Sustainability, 2024)
Many actions are underway at global, national, and local levels to increase plastics circularity.However, studies evaluating the environmental and socio-economic impacts of such a transition are lacking at regional levels in the U.S. In this work, the existing polyethylene terephthalate and polyolefin plastics supply chains in Michigan were compared to a potential future ('NextCycle') scenario that looks at increasing Michigan's overall recycling rate to 45%. Material flow analysis data was combined with environmental and socio-economic metrics to evaluate the sustainability of these supply chains for the modeled scenarios. Overall, the NextCycle scenario for these supply chains achieved a net 14% and 34% savings of greenhouse gas (GHG) emissions and energy impacts, when compared with their respective baseline values. Additionally, the NextCycle scenario showed a net gain in employment and wages, however, it showed a net loss of revenue generation outside of Michigan due to the avoided use of virgin resins in Michigan.